The Use of STEM (Science, Technology, Engineering, and Mathematics) Models to Improve Elementary School Science Concept Understanding - Ade Nira Susilawati; Bayu Kelana, Jajang; Ghiyats Ristiana, Muhammad (PPG IKIP Siliwangi, 2025)
Science learning in elementary schools aims to help students understand scientific concepts through observation and real experiences. This study aims to describe the improvement of fifth-grade elementary school students' conceptual understanding related to the properties of light through the application of the STEM (Science, Technology, Engineering, and Mathematics) learning model. SDN 2 Cilumba conducted the study, employing the pre-experimental method of a one-group pretest-posttest design. The instruments used included a concept understanding test and interviews. The results of data analysis showed a significant increase in students' average scores, from 58.81 (pretest) to 78.53 (posttest). The paired t-test produced a significance value of 0.000 < 0.05, indicating that the STEM model was effective in improving students' conceptual understanding. The results of the interviews revealed that students were enthusiastic about participating in STEM-based learning, even though teachers faced time constraints and students had difficulty restating concepts. Overall, the majority of students were in the good understanding category (60.01%), excellent (26.66%), and sufficient (13.33%). These findings reinforce that the STEM approach can be an alternative to meaningful and intriguing science learning at the elementary school level.